SOCIALIZATION OF STUNTING-FREE INDONESIA PROGRAM WITH ABCDE APPROACH AT AIR HITAM POSYANDU (Jurnal Abdimas Administrasi Kesehatan, 2022)
The purpose of socializing the stunting-free Indonesia program with the ABCDE approach at the Air Hitam Posyandu is to increase public knowledge about stunting prevention and handling. The method used in developing the potential of posyandu black water is the transfer of science and technology through health administration group learning techniques accompanied by practice. The result of the service that the socialization of the stunting-free Indonesian program with the ABCDE approach at the Air Hitam Posyandu went well.